New heat flux model for non-axisymmetric divertor infrared structures. (26th November 2020) - Wingen, A.; Orlov, D.; Evans, T.E.; Bykov, I.; Wilks, T.M.
Abstract: A convective heat flux model for perturbed plasmas, based on guiding center ion drift in vacuum fields (Wingen, et al 2014 Phys. Plasmas 21 012509), has been updated. The old model only considered ion heat flux, while here also electron heat flux is included. The updated model predicts divertor heat flux distributions in non-axisymmetric (3D) plasmas with applied resonant magnetic perturbation fields, and includes electric scalar potentials. It is found that a radial electric field in the near scrape-off layer can considerably shift the footprints toroidally, leading to a smearing out effect of the incident heat flux, while a simple model for sheath potential has little impact on footprints. Various approaches to model electron heat flux are studied. A convective electron model, based on collisionless free streaming, is found to yield the best agreement with measurements, while a conductive model requires a flat temperature gradient inside lobes to yield acceptable peak heat flux values. A heuristic heat flux layer approach, based on a fixed layer width also requires a limited heat flux inside the last closed flux surface (LCFS); by selecting various locations of the LCFS, the results of the conductive or convective model can be recovered respectively. The sum of ion and electron heat fluxes, both obtained by the convective model, is compared to experimental data for multiple time slices in DIII-D. Strike point splitting is observed with peak heat fluxes and layer widths that compare well to infrared camera measurements.